Substituting inpatient rehabilitation beds for home‐based multidisciplinary rehabilitation: A qualitative study of patient perceptions. (26th November 2020) - Kimmel, Lara A.; Burge, Angela; Watterson, Dina; Wolters, Catherine; Holland, Anne; Reed, Melanie; Hunter, Peter; Brookes, Belinda; Lee, Victoria; Leong, Ronald
Abstract: Objective: To understand the patients' perspectives of the pilot Better at Home program in order to inform the development of bed substitution rehabilitation services. Methods: Prospective qualitative study using semi‐structured interviews undertaken 3‐6 months following program participation was performed. Interviews were transcribed and themes developed by two independent researchers. Results: Nineteen participants (14 females) were interviewed. Major themes found included high satisfaction with the service and a high regard for the importance of communication both within the team and with the patients. Patients had inconsistent views on the provision of services with some feeling that the program was not specific to their needs, whilst others felt it was focused and flexible. Involvement in decision‐making for referral to the service was also not always fully understood. Conclusion: This study provides important information that can be utilised in the development of any bed substitution home‐based model of care.